Low-Mass Star Evolution: Third Dredge-up and Overshooting in the Asymptotic Giant Branch (AGB) Phase - Nasrul, Bayu Harnadi; Surungan, Tasrief (PILLAR OF PHYSICS, 2025)
Background. The Asymptotic Giant Branch (AGB) phase is a crucial stage in stellar evolution, marked by key nuclear fusion processes and structural changes. Important phenomena include Third dredge-up (TDU), where the shedding of outer layers characterizes material from the star's interior surfaces and mass loss. Aim. This study examines how overshooting parameter rates affect AGB evolution in a star with a mass of 1.85 M☉, focusing on TDU efficiency, its impact on the star's evolutionary path, and the effects of mass loss and structural changes. Methods. Stellar evolution simulations were performed using Module Experiment Stellar Astrophysics (MESA), exploring various overshooting parameters for the star models. Results. Increased overshooting improves mixing in convective zones, extends the AGB phase, and enhances TDU efficiency. As a result, the star evolves into a carbon-oxygen white dwarf (CO WD) with O-rich material at the core, influenced by mass loss and overshooting. Conclusion. Overshooting significantly affects AGB evolution in a 1.85 M☉ star by altering TDU behavior and mass loss patterns. These changes impact the star's final nuclear fusion composition, influencing its developmental path and ultimate characteristics.